2023
DOI: 10.3389/fphar.2023.1186905
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacy services for tuberculosis management: a systematic review

Abstract: Objective: This study aims to systematically review the content and potential effects of clinical pharmacy services in tuberculosis (TB) care management.Methods: Searches were performed in PubMed, Embase, Cochrane, Scopus, and Web of Science databases following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Study characteristics and outcomes were extracted, and clinical pharmacy service components were characterized using the Descriptive Elements of Pharmacist Intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The pivotal role of pharmacists in TB control initiatives aligns with broader efforts to engage all healthcare professionals in the fight against TB. As the most accessible healthcare providers and among the most trusted, pharmacists are uniquely positioned to contribute significantly to TB management (Iskandar et al, 2023 ; Wong et al, 2023 ; World Health Organization, International Pharmaceutical Federation, 2011 ). The primary objective of this systematic review was to evaluate the impact of PC interventions on enhancing clinical outcomes in individuals diagnosed with TB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pivotal role of pharmacists in TB control initiatives aligns with broader efforts to engage all healthcare professionals in the fight against TB. As the most accessible healthcare providers and among the most trusted, pharmacists are uniquely positioned to contribute significantly to TB management (Iskandar et al, 2023 ; Wong et al, 2023 ; World Health Organization, International Pharmaceutical Federation, 2011 ). The primary objective of this systematic review was to evaluate the impact of PC interventions on enhancing clinical outcomes in individuals diagnosed with TB.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacist involvement in TB programmes can improve continuity of care and bridge the gap between symptoms detection and monitoring of treatment (Wong et al, 2023 ). In addition, they play a crucial role in optimising therapy of patients after TB diagnosis, ensuring that appropriate patient-centred care is given, and minimising anti-TB drugs-related adverse effects (Iskandar et al, 2023 ; Miller & Goodman, 2020 ). Moreover, pharmacist play a role in directly observed therapy (DOT) strategy, which is a cornerstone in improving the outcomes of TB care (Wong et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Non-adherence to treatment is a significant factor causing inadequate drug effectiveness and adverse reactions, leading to drug resistance. 24 25 Pharmacist intervention through CPS can address these issues, [25][26][27][28] but its implementation is challenging 18 and requires a comprehensive and collaborative approach focusing on the unique traits of each patient. 2 7 Despite the limited number of patients receiving collaborative TB care, 9 we found that patients were the most likely to receive CPS, indicating their high involvement with pharmacists, and this could improve TB understanding and the quality of care, 29 30 motivating them to adhere to their treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews focused on pharmacists’ role in treating TB [ 16 ]; however, there is a paucity of studies to focus on pharmacist roles in overall TB elimination efforts, particularly regarding actions beyond the core of pharmaceutical care, i.e., the interpersonal level.…”
Section: Introductionmentioning
confidence: 99%